Polyhydroxyalkanoates from Palm Oil: Biodegradable Plastics - Sudesh, Kumar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The environmental problems caused by petroleum-based plastic and plastic waste have led to an increasing demand for biobased and biodegradable plastics, such as polyhydroxyalkanoates (PHAs). These polyesters are synthesized from carbon sources, e.g. sugar and plant oils, by various bacteria. This book highlights the potential of plant oils, especially palm oil, as a feedstock for PHA production. In addition, new PHA applications are discussed and the sustainability of PHA production from plant oils is critically examined.
Introduction -- Bio-based and Biodegradable Polymers -- Plant Oils and Agricultural By-Products as Carbon Feedstock for PHA Production -- Is Palm Oil Produced in a Sustainable Manner? Jatropha Oil as a Potential Carbon Soruce for PHA Production -- Potenial Applications of PHA -- Summary and Future Outlook.
Keywords: Life sciences; Microbiology; Polymers; Biotechnology; Sustainable development; Life Sciences; Microbiology; Applied Microbiology; Environmental Engineering/Biotechnology.; Sustainable Development; Polymer Sciences